Effect of urea and ammonium chloride onAspartate and Alanine transaminases ofOreochromis mossambicus (Peters) - Vijayavel, K; Balasubramanian, S E; Balasubramanian, M P (Indian Journal of Fisheries, 2011)
The effect of urea and ammonium chloride on transaminases was studied inserum, liver and muscle of fresh water fish Oreochromis mossabicus. Therewas an over all increase in the aspartate and alanine transaminase in serum,liver and muscle subjected to urea and ammonium chloride individually and incombinations for 96 h.